Effect of morphology on the near infrared shielding property and thermal performance of K0.3WO3 blue pigments for smart window applications. (September 2018) - Cai, Ligang; Wu, Xiaomei; Gao, Qiang; Fan, Yueming
Abstract: Different shaped K0.3 WO3 blue pigments were prepared by a simple solvothermal method. The as-synthesized K0.3 WO3 pigments were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, and spectrophotometer. It's found that the concentration of WCl6 had a great influence on the morphology of K0.3 WO3 pigments. Spindlelike K0.3 WO3 composed of nanorods, microsphere structures composed of nanorods and microflower structures composed of nanosheets could be obtained with an increasing WCl6 concentration. The obtained spindle shaped K0.3 WO3 showed higher near infrared shielding ability than that of K0.3 WO3 microspheres and microflowers. The reason could be attributed to the enhanced local surface plasmon resonance absorption induced by higher aspect ratio and higher free carrier concentrations of spindleliked K0.3 WO3 . An approximately 8.5 °C decrease in inner temperature was obtained for the heat box covered with K0.3 WO3 coated glass. Therefore, the synthesized K0.3 WO3 blue pigments with high visible light transparency and high near infrared shielding ability have the potential to be applied in smart window coatings to reduce the heat build-up. Graphical abstract: Highlights: Different shaped K0.3 WO3 blue pigments were prepared. The morphology has a great influence on the NIR shielding property. The NIR shielding ability of K0.3 WO3 pigments was as high as 65.9%. The visible light transparency of K0.3 WO3 pigment was as high as 62.4%.